Exploring implementation of an electronic referral management system and enhanced primary care service for oral surgery: perspectives of patients, providers and practitioners - Joanna Goldthorpe; Caroline Sanders; Richard Macey; Lesley Gough; Jean Rogers; Martin Tickle; Iain Pretty (BMC, 2018)
Abstract Background A specialist primary care oral surgery service combined with an electronic referral management and triage system was developed in response to concerns raised around overburdened secondary care services in the UK. Whilst the system has the potential to manage conflicting demand for oral surgery services against an objective need, the new pathway represents a number of challenges to existing working practices and could compromise the sustainability of existing hospital services. The aim of this research was to carry out a qualitative exploration of implementation of a new intervention to gain insight into how these challenges have manifested and been addressed. Methods Views were sought from stakeholders (dentists, hospital staff, commissioners and patients) at various time points over 3 years during and after implementation using semi-structured interviews. Normalization Process Theory informed a qualitative thematic analysis which was carried out using data from interview transcripts to identify important emerging issues. Results Themes emerging from the data were; amenability to change and assimilation into practice (primary care dentists), compliance and governance, changing perceptions of impact (secondary care staff and commissioners) understanding change in service provision and priorities for treatment (patients). The new pathway impacted stakeholders at different stages of implementation. Conclusion Electronic referral management with a primary care advanced service for oral surgery was successfully implemented in a specific area of the UK. The service model evaluated has the potential to be expanded across a wider geographical footprint and to support demand management in other specialist services.